Instagram and its effect on customer loyalty in insurance brokers in Manta-Ecuador. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2025)
The present research aims to analyze how the social network Instagram achieves an attractive effect on customers of insurance brokers, it is proposed to explore in depth the dynamics of insurance brokers on Instagram; the objective is to create through the social network a striking effect and that customers know in depth the products and services provided by insurance brokers; the research is exploratory descriptive, field and bibliographic methods were applied quali-quantitative methods using IBM SPSS 27 statistical program. As a result, insurance brokers in Manta tend to use Instagram with little regularity, limiting the knowledge about the services provided, which means their work to teach and familiarize users with the insurance market.
Keywords: Instagram; Branding; Insurance brokers; Loyalty; Service